Addition-curable silicone composition, method for producing the same and optical semiconductor device

The addition-curable silicone composition with surface-treated inorganic oxide particles addresses the limitations of conventional resins by providing a cured product with improved mechanical properties, heat resistance, and moisture resistance for optical semiconductor devices.

JP2025008685APending Publication Date: 2025-01-20SHIN ETSU CHEMICAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023111054
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Conventional thermoplastic resins used in optical semiconductor devices face issues with heat resistance, moisture resistance, and color fastness under long-term usage conditions, especially when using lead-free solder, leading to deformation and yellowing, while silicone resins suffer from high gas permeability and mechanical property deterioration.

Method used

An addition-curable silicone composition containing surface-treated inorganic oxide particles with a polysilazane compound, characterized by specific ratios of organopolysiloxane, organosilicon compound, platinum group metal catalyst, and inorganic oxide particles, which improves mechanical properties, crack resistance, and moisture resistance.

Benefits of technology

The composition provides a cured product with excellent workability, mechanical properties, heat resistance, and moisture resistance, suitable for optical semiconductor devices, enhancing their reliability under high temperature and humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008685000001
    Figure 2025008685000001
  • Figure 2025008685000002
    Figure 2025008685000002
  • Figure 2025008685000003
    Figure 2025008685000003
Patent Text Reader

Abstract

To provide an addition-curable silicone composition which contains inorganic oxide particles and enables a cured product to have excellent mechanical properties, crack resistance, heat resistance and moisture resistance and a composition to have low viscosity and excellent workability.SOLUTION: There is provided an addition-curable silicone composition which is a surface-treated inorganic oxide particle obtained by surface treated by (A) an organopolysiloxane having two or more alkenyl groups bonded to a silicon atom in one molecule, (B) an organosilicon compound having two or more silicon atom-bonded hydrogen atoms in one molecule, (C) a platinum group metal-based catalyst and (D) a polysilazane compound-containing composition which is an inorganic oxide particle and contains a polysilazane compound having a ratio of the number of repeating units represented by the formula (2) to the total number of repeating units represented by following formulas (1) and (2) of 0 to 0.5 and an organic solvent. (wherein, R is a group selected from an aliphatic hydrocarbon group, an aromatic hydrocarbon group and an alkoxy group.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an addition-curable silicone composition, a method for producing the same, and an optical semiconductor device. [Background technology]

[0002] Resins used in optical semiconductor devices are required to have high transparency, high refractive index, high heat dissipation, high reflectance, mechanical properties, heat resistance, weather resistance, and gas barrier properties according to the application, and thermoplastic resins such as epoxy resins, poly(meth)acrylates, and polycarbonates have been widely used in the past. However, with the recent trend toward higher output of optical semiconductor devices, it has become clear that problems with heat resistance, moisture resistance, and discoloration resistance arise when these thermoplastic resins are used under long-term usage conditions.

[0003] Recently, lead-free solder has come to be used more and more often when soldering optical elements to substrates. This lead-free solder has a higher melting temperature than conventional solder, and soldering must usually be performed at a temperature of 260°C or higher, but it has become clear that when soldering is performed at such a temperature, problems occur such as deformation occurring in the conventional thermoplastic resin sealing materials mentioned above, and the sealing materials turning yellow due to the high temperature.

[0004] Thus, with the increase in the output of optical semiconductor devices and the use of lead-free solder, encapsulants are required to have better heat resistance, moisture resistance, and discoloration resistance than ever before. Up until now, optical resin compositions in which nanosilica is filled into thermoplastic resins for the purpose of improving heat resistance have been proposed (Patent Documents 1 and 2), but the thermoplastic resins themselves have limitations in terms of heat resistance, and sufficient heat resistance to meet the requirements has not been obtained.

[0005] Silicone resin, a thermosetting resin, is considered as a material for optical semiconductor devices because of its excellent heat resistance, light resistance, and light transmission. However, this silicone resin has very high gas permeability (i.e., low gas barrier properties) when used alone, and the electrodes are deteriorated by the effects of gases such as oxygen and moisture in the air that permeate (Patent Documents 3 and 4).

[0006] In addition, although gas permeability is reduced by filling with inorganic oxides, oxygen and moisture in the air at high temperatures or high humidity can cause rapid deterioration of the silicone resin via the inorganic oxide particles, and even when inorganic oxide particles that have been treated in a specific manner, such as commercially available inorganic oxide particles, are used, the problems of cracks occurring due to a decrease in mechanical properties and an increase in hardness cannot be improved (Patent Documents 5 to 7).

[0007] As a countermeasure, the introduction of aromatic substituents such as phenyl groups to improve gas barrier properties has been investigated, but the introduction of aromatic substituents increases the change in viscoelasticity when heated, resulting in problems such as a further decrease in crack resistance compared to methylsilicone resins, more pronounced yellowing, and decreased heat and light resistance (Patent Document 8).Therefore, there is a demand for the development of materials for optical semiconductor devices that are easy to work with and have excellent mechanical properties, crack resistance, heat resistance, and moisture resistance when cured. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2012-214554 A [Patent Document 2] JP 2013-204029 A [Patent Document 3] JP 2006-213789 A [Patent Document 4] JP 2007-131694 A [Patent Document 5] JP 2011-099008 A [Patent Document 6] JP 2015-051924 A [Patent Document 7] JP 2014-125401 A [Patent Document 8] Special Publication No. 2017-519058 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in view of the above problems, and aims to provide an addition-curable silicone composition containing inorganic oxide particles, which can provide a cured product having excellent mechanical properties, crack resistance, heat resistance, and moisture resistance, and can provide a composition with low viscosity and excellent workability, and to provide an optical semiconductor device including a cured product obtained by curing the composition. The present invention also provides a method for producing such an addition-curable silicone composition. [Means for solving the problem]

[0010] In order to solve the above problems, the present invention provides (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in the component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in the component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles An addition-curable silicone composition comprising: The inorganic oxide particles are surface-treated inorganic oxide particles that contain a polysilazane compound and an organic solvent, in which the ratio of the number of repeating units represented by the following formula (2) to the total number of repeating units represented by the following formulas (1) and (2) is 0 to 0.5, and the polysilazane compound is present in an amount of 0.1 to 20 mass% relative to the total amount of the polysilazane compound and the organic solvent. [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and R in one molecule of the polysilazane compound may be the same or different.)

[0011] An addition-curable silicone composition that uses such surface-treated inorganic oxide particles can provide a composition with excellent workability, and a cured product with excellent mechanical properties, crack resistance, heat resistance, and moisture resistance.

[0012] In addition, R in the formula (2) of the polysilazane compound is preferably a methyl group.

[0013] Such a polysilazane compound having a methyl group can be easily prepared.

[0014] The polysilazane compound-containing composition preferably contains a curing catalyst.

[0015] Such a material allows surface treatment at room temperature in a short period of time, and is also excellent in workability.

[0016] The inorganic oxide particles preferably contain at least one of silicon dioxide, zirconium oxide, titanium oxide, aluminum oxide, and zinc oxide.

[0017] When such surface-treated inorganic oxide particles are added to an addition-curable silicone composition, they can have excellent mechanical properties, crack resistance, heat resistance, moisture resistance, and workability.

[0018] The present invention also provides an optical semiconductor device comprising a cured product obtained by curing the above-mentioned addition-curable silicone composition.

[0019] In such a semiconductor device, the semiconductor element is encapsulated with a cured product that has excellent mechanical properties, crack resistance, heat resistance, and moisture resistance, resulting in an optical semiconductor device with excellent long-term reliability and long-term color rendering properties under high temperature and high humidity conditions.

[0020] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in the component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in the component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles A method for producing an addition-curable silicone composition comprising the steps of: providing the inorganic oxide particles; a step of preparing surface-treated inorganic oxide particles by surface-treating the inorganic oxide particles with a polysilazane compound-containing composition containing a polysilazane compound and an organic solvent, the polysilazane compound being present in an amount of 0.1 to 20 mass% relative to the total amount of the polysilazane compound and the organic solvent, the polysilazane compound being in a ratio of 0.5 to 0.5, and the inorganic oxide particles being in a ratio of 0.1 to 20 mass% relative to the total amount of the polysilazane compound and the organic solvent; a step of producing the addition-curable silicone composition by mixing the surface-treated inorganic oxide particles with the components (A) to (C); The present invention provides a method for producing an addition-curable silicone composition comprising the steps of: [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and R in one molecule of the polysilazane compound may be the same or different.)

[0021] A method for producing an addition-curable silicone composition using such surface-treated inorganic oxide particles can provide a composition with excellent workability and a cured product with excellent mechanical properties, crack resistance, heat resistance, and moisture resistance. Effect of the Invention

[0022] The addition-curable silicone composition of the present invention, which contains inorganic oxide particles, can provide an addition-curable silicone composition that is excellent in workability and in mechanical properties, crack resistance, heat resistance, and moisture resistance of the cured product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] As described above, in order to meet the operating conditions of recent semiconductor devices, there is a demand for improved heat resistance, moisture resistance, workability, and the like.

[0024] As a result of intensive research aimed at solving the above problems, the present inventors have found that, when an addition-curable silicone composition containing surface-treated inorganic oxide particles that have been surface-treated with a polysilazane compound-containing composition satisfying a modification rate within a prescribed range is added, the cured product can have excellent mechanical properties, crack resistance, heat resistance, and moisture resistance, and that even after the addition of the inorganic oxide particles, the composition can have a low viscosity and excellent workability, and further, such an addition-curable silicone composition can be suitably used for optical semiconductor elements such as LEDs, thereby completing the present invention.

[0025] That is, the present invention provides: (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in the component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in the component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles An addition-curable silicone composition comprising: The inorganic oxide particles are surface-treated inorganic oxide particles that contain a polysilazane compound and an organic solvent, in which the ratio of the number of repeating units represented by the following formula (2) to the total number of repeating units represented by the following formulas (1) and (2) is 0 to 0.5, and the polysilazane compound is present in an amount of 0.1 to 20 mass% relative to the total amount of the polysilazane compound and the organic solvent. [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and R in one molecule of the polysilazane compound may be the same or different.) This provides:

[0026] In addition, as a method for producing such an addition-curable silicone composition, the following method for producing an addition-curable silicone composition is provided. (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in the component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in the component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles A method for producing an addition-curable silicone composition comprising the steps of: providing the inorganic oxide particles; a step of preparing surface-treated inorganic oxide particles by surface-treating the inorganic oxide particles with a polysilazane compound-containing composition containing a polysilazane compound and an organic solvent, the ratio of the number of repeating units represented by formula (2) to the total number of repeating units represented by formulas (1) and (2) being 0 to 0.5, and the polysilazane compound being 0.1 to 20 mass% based on the total amount of the polysilazane compound and the organic solvent; a step of producing the addition-curable silicone composition by mixing the surface-treated inorganic oxide particles with the components (A) to (C); The present invention relates to a method for producing an addition-curable silicone composition, the method comprising the steps of:

[0027] The present invention will be described in detail below, but the present invention is not limited thereto.

[0028] The addition-curable silicone composition of the present invention contains the above-mentioned components (A) to (D), and may further contain various known additives as necessary. Each component will be described below.

[0029] [(A): Organopolysiloxane] The component (A) of the present invention is an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms in each molecule, and may be any organopolysiloxane, such as a linear or branched one. As the alkenyl group, an alkenyl group having 2 to 10 carbon atoms, such as a vinyl group or an allyl group, is preferred, and is particularly preferred if it has 2 to 8 carbon atoms.

[0030] The linear organopolysiloxane typically has a weight average molecular weight (Mw) of 1,500 to 300,000, and preferably 2,000 to 200,000. If the molecular weight is 1,500 or more, there is no risk that the composition will not cure, and if the molecular weight is 300,000 or less, there is no risk that the composition will become unnecessarily viscous and will not flow.

[0031] The weight average molecular weight (Mw) of the organopolysiloxane referred to in this specification refers to the weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions using polystyrene as the standard substance. [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) ·Flow rate: 0.6mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L ·TSKgel SuperH4000(6.0mmI.D.×15cm×1) ·TSKgel SuperH3000(6.0mmI.D.×15cm×1) ·TSKgel SuperH2000(6.0mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (0.5 wt% THF solution)

[0032] Specific examples of the above-mentioned linear organopolysiloxane having an alkenyl group include the following.

[0033] [ka]

[0034] The branched organopolysiloxane that can be used as component (A) of the present invention is SiO 4 / 2 Units and R 1 SiO 3 / 2The branched-chain organopolysiloxane contains either one or both of the units and has two or more alkenyl groups bonded to silicon atoms in one molecule. In this case, R 1 are preferably independently a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms.

[0035] The branched-chain organopolysiloxane as component (A) of the present invention has two or more alkenyl groups bonded to silicon atoms in one molecule, and the amount of the alkenyl groups contained is preferably 0.01 to 0.5 mol / 100 g, more preferably 0.05 to 0.3 mol / 100 g, and even more preferably 0.10 to 0.25 mol / 100 g. If the amount of alkenyl groups bonded to silicon atoms is 0.01 mol / 100 g or more, there are many crosslinks and the composition hardens, and if it is 0.5 mol / 100 g or less, the crosslink density is appropriate and toughness can be ensured.

[0036] Furthermore, the amount of hydroxyl groups bonded to silicon atoms is preferably 0.001 to 1.0 mol / 100 g, more preferably 0.005 to 0.8 mol / 100 g, and even more preferably 0.008 to 0.6 mol / 100 g.

[0037] In the branched organopolysiloxane of the present invention as component (A), the amount of alkoxy groups bonded to silicon atoms having 1 to 10 carbon atoms, preferably 1 to 5 carbon atoms, is preferably 1.0 mol / 100 g or less, more preferably 0.8 mol / 100 g or less, and even more preferably 0.5 mol / 100 g or less. If the amount of alkoxy groups is 1.0 mol / 100 g or less, no alcohol gas is generated as a by-product during curing, and no voids remain in the cured product.

[0038] In the present invention, the amount of hydroxyl groups and alkoxy groups bonded to silicon atoms is 1 H-NMR and 29 This refers to the value measured by Si-NMR.

[0039] The branched-chain organopolysiloxane as component (A) of the present invention further contains 0 to 60 mol %, preferably 0 to 50 mol % of SiO 4 / 2 unit (Q unit), 0 to 90 mol%, preferably 30 to 80 mol% of R 1a SiO 3 / 2 units (T units) and 0 to 50 mol%, preferably 0 to 30 mol% of (R 1a ) 3 SiO 1 / 2 It is preferable that the organopolysiloxane has a resin structure composed of SiO 4 / 2 Units and R 1a SiO 3 / 2 The sum of the units is preferably 50 mol % or more. 1a are independently a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, preferably 2 to 5 carbon atoms, an aryl group having 6 to 10 carbon atoms, preferably 6 to 8 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms; 1a At least one of them is preferably an alkenyl group having 2 to 10 carbon atoms.

[0040] R in M ​​and T units 1a are each independently a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms, and specific examples thereof include lower alkyl groups such as methyl, ethyl, propyl, and butyl groups; cycloalkyl groups such as cyclohexyl groups; aryl groups such as phenyl, tolyl, and xylyl groups; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl groups; alkenyl groups such as vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, cyclohexenyl, and octenyl groups; and groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms such as fluorine, bromine, and chlorine, or with cyano groups, such as chloromethyl, cyanoethyl, and 3,3,3-trifluoropropyl groups. Among these, methyl, phenyl, and vinyl groups are preferred.

[0041] SiO 4 / 2Examples of materials for obtaining the unit (Q unit) include, but are not limited to, sodium silicate, tetraalkoxysilane, and condensation products thereof.

[0042] R 1a SiO 3 / 2 Examples of materials for obtaining units (T units) include, but are not limited to, organosilicon compounds such as organotrichlorosilane and organotrialkoxysilane represented by the following structural formulas, and condensation products thereof. [ka] (In the above formula, Me represents a methyl group.)

[0043] (R 1a ) 3 SiO 1 / 2 Examples of materials for obtaining units (M units) include organosilicon compounds such as triorganochlorosilane, triorganoalkoxysilane, and hexaorganodisiloxane, which are represented by the following structural formulas, but are not limited to these. [ka] (In the above formula, Me represents a methyl group.)

[0044] [(B) Organohydrogenpolysiloxane] The component (B) of the present invention is an organosilicon compound having two or more silicon-bonded hydrogen atoms (hydrogen atoms bonded to silicon atoms) in one molecule, i.e., an organohydrogenpolysiloxane. In other words, the component (B) of the present invention is an organohydrogenpolysiloxane having two or more SiH groups (hydrosilyl groups) in one molecule, and reacts with the component (A) to act as a crosslinking agent.

[0045] Component (B) can be represented by the following average composition formula (3). R 2 h H i SiO (4-h-i) / 2 (3)

[0046] In the average composition formula (3), R 2 are the same or different unsubstituted or substituted monovalent hydrocarbon groups having 1 to 10 carbon atoms, and h and i are positive numbers satisfying 0.7≦h≦2.1, 0.001≦i≦1.0 and 0.8≦h+i≦3.0, and preferably 1.0≦h≦2.0, 0.01≦i≦1.0 and 1.5≦h+i≦2.5.

[0047] Above R 2 Examples of the alkyl group include saturated aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, and pentyl groups, saturated cyclic hydrocarbon groups such as cyclopentyl and cyclohexyl groups, aryl groups such as phenyl, tolyl, and xylyl groups, and aralkyl groups such as benzyl, phenylethyl, and phenylpropyl groups, as well as aromatic hydrocarbon groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with halogen atoms such as fluorine, bromine, and chlorine, for example, halogenated hydrocarbon groups such as trifluoropropyl and chloropropyl groups, and epoxy groups such as allylglycidyl groups. Among these, saturated aliphatic hydrocarbon groups having 1 to 5 carbon atoms such as methyl, ethyl, and propyl groups, and phenyl groups are preferred.

[0048] The molecular structure of component (B) is not particularly limited, and any molecular structure, such as linear, cyclic, branched, or three-dimensional network (resin-like), can be used as component (B). When component (B) has a linear structure, the hydrosilyl group may be bonded to silicon atoms only at either the molecular chain terminal or the molecular chain side chain, or may be bonded to silicon atoms at both. In addition, the number of silicon atoms (or degree of polymerization) in one molecule is usually 2 to 200, preferably about 3 to 100, and organohydrogenpolysiloxanes that are liquid or solid at room temperature (25°C) can be used.

[0049] Specific examples of organohydrogenpolysiloxanes represented by the above average composition formula (3) include tris(hydrogendimethylsiloxy)phenylsilane, copolymers of methylhydrogensiloxane and diphenylsiloxane capped at both ends with trimethylsiloxy groups, copolymers of methylhydrogensiloxane, diphenylsiloxane and dimethylsiloxane capped at both ends with trimethylsiloxy groups, copolymers of methylhydrogensiloxane, methylphenylsiloxane and dimethylsiloxane capped at both ends with trimethylsiloxy groups, copolymers of methylhydrogensiloxane, dimethylsiloxane and diphenylsiloxane capped at both ends with dimethylhydrogensiloxy groups, copolymers of methylhydrogensiloxane, dimethylsiloxane and diphenylsiloxane capped at both ends with dimethylhydrogensiloxy groups, and copolymers of methylhydrogensiloxane, dimethylsiloxane and methylphenylsiloxane capped at both ends with dimethylhydrogensiloxy groups, (CH 3 ) 2 HSiO 1 / 2 Units and SiO 4 / 2 Units and (C 6 H 5 ) 3 SiO 1 / 2 and copolymers consisting of units.

[0050] In addition, organohydrogenpolysiloxanes represented by the following structures can also be used, but are not limited to these. [ka] (In the formula, p, r, and s are each an integer of 0 or more, and q is an integer of 1 or more.)

[0051] The amount of component (B) added is an amount such that the amount of hydrosilyl groups of component (B) is 0.1 to 4.0 moles, more preferably 0.5 to 3.5 moles, and even more preferably 0.8 to 3.0 moles per mole of alkenyl groups bonded to silicon atoms in component (A).

[0052] If the amount of hydrosilyl groups in the (B) component is 0.1 mol or more, the curing reaction of the composition of the present invention proceeds, and a cured product can be obtained, and the crosslink density and mechanical strength of the obtained cured product are sufficient, and the heat resistance is also improved. On the other hand, if the amount of the hydrosilyl groups is 4.0 mol or less, a large amount of unreacted hydrosilyl groups do not remain in the cured product, so that there is no change in physical properties over time or a decrease in the heat resistance of the cured product, and further, no foaming due to dehydrogenation occurs in the cured product.

[0053] [(C) Platinum group metal catalyst] The component (C) in the present invention is a platinum group metal catalyst, and any of the conventionally known catalysts that promote the hydrosilylation reaction of the components (A) and (B) can be used. In consideration of cost, etc., platinum-based catalysts such as platinum, platinum black, and chloroplatinic acid, for example, H 2 PtCl 6 pH 2 OK 2 PtCl 6 ,KHPtCl 6 pH 2 OK 2 PtCl 4 ,K 2 PtCl 4 pH 2 O,PtO 2 pH 2 O,PtCl 4 pH 2 O,PtCl 2 ,H 2 PtCl 4 pH 2 Examples of catalysts include platinum, platinum complexes with hydrocarbons such as olefins, alcohols, or vinyl group-containing organopolysiloxanes, and photoactive complexes such as trimethyl(methylcyclopentadienyl)platinum. These catalysts may be used alone or in combination of two or more. The amount of these catalysts to be added may be an effective amount for curing, and is usually preferably 0.1 to 500 ppm by mass of platinum group metal relative to the total amount of components (A) and (B), and particularly preferably 0.5 to 100 ppm by mass.

[0054] [(D) Inorganic oxide particles] As the inorganic oxide particles of component (D), surface-treated inorganic oxide particles are used. This surface treatment will be described later. The blending amount of component (D) is preferably 1 to 99 mass% based on the total amount of the composition, more preferably 25 to 75 mass%, and even more preferably 30 to 70 mass%. The component (D) may be blended alone or in combination of two or more types. When the blending amount of component (D) is 1 mass% or more, the effect of the inorganic oxide particles can be sufficiently obtained, and when the blending amount is 99 mass% or less, the effect of the silicone can be sufficiently obtained, and the durability of the optical semiconductor device using the cured product can be improved.

[0055] Examples of inorganic oxide particles include silicon dioxide (silica: SiO 2 ), zirconium oxide (zirconia: ZrO 2 ), titanium dioxide (TiO 2 ), aluminum oxide (alumina: Al 2 O 3 ), zinc oxide (ZnO), iron oxide (FeO 2 ), triiron tetroxide (Fe 3 O 4 ), lead oxide (PbO 2 ), tin oxide (SnO 2 ), cerium oxide (CeO 2 ), calcium oxide (CaO), manganese tetroxide (Mn 3 O 4 ), magnesium oxide (MgO), etc. These inorganic oxide particles can be used alone or in combination of two or more. Among these, silicon dioxide, zirconium oxide, titanium oxide, aluminum oxide, and zinc oxide are preferred, and titanium oxide is particularly preferred. By using these inorganic oxide particles, the properties of the cured product when added to a silicone resin composition can be further improved.

[0056] [Polysilazane] Polysilazane is a component that hardens to form a coating (cured film) on the surface of inorganic oxide particles. The polysilazane compound used in the present invention has a repeating unit represented by the following formula (1) and a repeating unit represented by the following formula (2). [ka]

[0057] In the formula (2), R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms. This R is preferably a group selected from an aliphatic hydrocarbon group having 1 to 3 carbon atoms, an aromatic hydrocarbon group having 6 to 8 carbon atoms, and an alkoxy group having 1 to 3 carbon atoms, such as a methyl group, an ethyl group, a phenyl group, a methoxy group, and an ethoxy group. Among them, a methyl group is particularly preferred because it is easy to handle and the hardness of the cured film is not easily reduced. R can be appropriately selected for each repeating unit in one molecule of polysilazane, and may be the same or different.

[0058] In addition, the polysilazane compound has a ratio of the number of repeating units represented by the formula (2) to the total number of repeating units represented by the formulas (1) and (2) of 0 to 0.5. If this ratio exceeds 0.5, the cured film contains a large amount of organic components, which may lead to a decrease in heat resistance. If this ratio is 0, that is, a polysilazane compound consisting of repeating units represented by the formula (1) may be used.

[0059] From the viewpoint of solubility in an organic solvent, which is a component of a dilution solvent, the polysilazane compound preferably has a weight-average molecular weight in the range of 200 to 1,000,000, more preferably 500 to 100,000, and even more preferably 1,000 to 20,000. If the weight-average molecular weight is 200 or more, the volatility is not high and there is almost no volatilization during drying of the organic solvent and surface treatment, so that a uniform surface treatment of inorganic oxide particles is possible. If the weight-average molecular weight is 1,000,000 or less, the solubility in an organic solvent is good and the dissolution viscosity is not high, so that an efficient surface treatment can be performed.

[0060] The weight average molecular weight of the polysilazane compound referred to in this specification refers to the weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions using polystyrene as a standard substance. [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.6mL / min Detector: UV detector Column: TSK Guardcolumn SuperH-L TSKgel SuperMultiporeHZ-M(4.6mmI.D.×15cm×4) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (THF solution with a concentration of 0.5% by mass)

[0061] The polysilazane compound having the repeating units represented by the formula (1) and the formula (2) may contain a branched structure or a cyclic structure in addition to these repeating units.

[0062] In addition, the polysilazane compound-containing composition contains the polysilazane compound in an amount of 0.1 to 20% by mass, and more preferably 0.5 to 10% by mass, based on the total amount of the polysilazane compound and the organic solvent. Within this range, the surfaces of inorganic oxide particles can be uniformly treated.

[0063] [Organic solvents] The polysilazane compound used in the present invention is diluted with an organic solvent for the purpose of improving storage stability and uniformity of surface treatment. The organic solvent is not particularly limited as long as it dissolves the polysilazane compound. For example, saturated aliphatic hydrocarbons such as n-pentane, isopentane, n-hexane, isohexane, n-heptane, isoheptane, n-octane, isooctane, n-nonane, isononane, n-decane, and isodecane; unsaturated aliphatic hydrocarbons such as 1-octene, 1-nonene, 1-decene, 1-dodecene, and β-myrcene; saturated alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, and decahydronaphthalene; unsaturated alicyclic hydrocarbons such as cyclohexene; terpene compounds such as p-menthane, d-limonene, l-limonene, and dipentene; aromatic hydrocarbons such as benzene, toluene, xylene, ethylbenzene, diethylbenzene, trimethylbenzene, triethylbenzene, and tetrahydronaphthalene; acetone, methylbenzene, ethylbenzene, diethylbenzene, trimethylbenzene, triethylbenzene, and tetrahydronaphthalene; ketone compounds such as n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, isoamyl acetate, ethyl acetoacetate, and ethyl caproate; alkyl ether compounds such as diethyl ether, di-n-propyl ether, di-n-butyl ether, di-n-pentyl ether, di-n-hexyl ether, and tert-butyl methyl ether; aryl ether compounds such as anisole and diphenyl ether; and glycol ether compounds such as bis(2-methoxyethyl)ether, bis(2-ethoxyethyl)ether, and bis(2-butoxyethyl)ether.

[0064] The polysilazane compound-containing composition preferably contains 1,000 ppm or less of water, more preferably 500 ppm or less of water, which is preferable because the polysilazane compound does not react with water, and therefore there is no risk of heat generation, generation of hydrogen gas or ammonia gas, thickening, gelation, etc.

[0065] [Curing catalyst] The polysilazane compound-containing composition used in the present invention may contain a curing catalyst in addition to the polysilazane compound and the organic solvent. The addition of the curing catalyst can increase the reaction rate of the polysilazane with the inorganic surface, which is preferable from the viewpoint of workability.

[0066] The curing catalyst is preferably, for example, an organosilicon compound having one or more alkoxysilyl groups and one or more amino groups in one molecule, or a compound containing a metal element.

[0067] Specific examples of the organosilicon compound include aminosilanes such as 3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, and 3-(2-aminoethylamino)propylmethyldiethoxysilane, as well as partial hydrolysates of these aminosilanes. Of these, 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane are preferred because of their fast curing rate and excellent workability.

[0068] Specific examples of the metal element-containing compound include compounds containing metal elements such as titanium, aluminum, tin, zinc, and palladium, and metal compounds of titanium and aluminum that are unlikely to cause coloring are preferred.

[0069] The curing catalyst may be added alone or in any combination of two or more kinds in any ratio. The amount of the curing catalyst added is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, based on 100 parts by mass of the polysilazane compound.

[0070] As a method for treating the surface of the inorganic oxide particles, a known method can be used. The surface treatment method includes a dry method and a wet method, but from the viewpoints of uniform treatment of the inorganic oxide particles and prevention of gelation, a wet method using a solution is preferred.

[0071] The surface treatment method is preferably a method for producing surface-treated inorganic oxide particles, which comprises reacting the above-mentioned specified inorganic oxide particles with a solution containing the above-mentioned specified polysilazane compound at 20°C to 150°C for 1 to 48 hours and performing a heat treatment at 100°C to 400°C.

[0072] This surface treatment can be performed at a sufficiently high speed if the reaction is performed at a temperature of 20° C. or higher, and the reaction can be easily controlled and gelation and coloring can be prevented if the reaction is performed at a temperature of 150° C. or lower. In addition, the treatment is likely to be sufficient if the reaction is performed for 1 hour or more, and production efficiency can be improved if the reaction is performed for 48 hours or less.

[0073] In addition to the above components (A) to (D), known adhesion promoters and additives can also be blended into the addition-curable silicone composition of the present invention, if necessary.

[0074] [Adhesion promoter] Examples of adhesion promoters include phenyltrimethoxysilane, trimethoxysilane, triethoxysilane, methyldimethoxysilane, diphenyldimethoxysilane, methylphenyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and oligomers thereof. These adhesion promoters can be used alone or in combination of two or more. The adhesion promoter is preferably 0 to 10% by mass, more preferably 0 to 5% by mass, based on the total mass of the above components (A) to (D).

[0075] [Other additives] Other additives include, for example, reinforcing inorganic fillers such as glass fiber, fumed silica, and fumed titanium oxide; inorganic white pigments such as calcium carbonate, magnesium oxide, aluminum hydroxide, barium carbonate, magnesium silicate, zinc sulfate, and barium sulfate; non-reinforcing inorganic fillers such as calcium silicate, carbon black, cerium fatty acid salts, barium fatty acid salts, cerium alkoxides, and barium alkoxides; silver (Ag), aluminum (Al), aluminum nitride (AlN), boron nitride (BN), and iron oxide (Fe 2 O 3 ), triiron tetroxide (Fe 3 O 4 ), lead oxide (PbO 2 ), tin oxide (SnO 2 ), cerium oxide (Ce 2 O 3、 CEO 2 ), calcium oxide (CaO), manganese tetroxide (Mn 3 O 4 These can be appropriately blended in an amount of up to 600 parts by mass, preferably 10 to 400 parts by mass, per 100 parts by mass of the combined total of the above components (A) to (D).

[0076] The addition curable silicone composition of the present invention can be cured after being applied to a predetermined substrate according to the application. As for the curing conditions, the composition can be sufficiently cured at room temperature (25°C), but may be cured by heating if necessary. When heating, the composition can be cured at a temperature of, for example, 60 to 200°C.

[0077] The addition-curable silicone composition of the present invention can be used in a variety of applications, including, but not limited to, sealing materials, adhesives, electrical insulating materials, laminates, coatings, inks, paints, sealants, resists, composite materials, films, underfill materials, anti-reflective materials, light diffusing materials, and light reflective materials.

[0078] The present invention also provides an optical semiconductor device in which a semiconductor element is encapsulated with a cured product of the above-mentioned addition-curable silicone composition of the present invention.

[0079] The addition-curable silicone composition of the present invention provides a cured product that has excellent mechanical properties, crack resistance, heat resistance, moisture resistance, and light resistance. EXAMPLES

[0080] The present invention will be specifically described below with reference to Synthesis Examples, Comparative Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. Note that parts indicate parts by mass, and the viscosity of each component indicates the absolute viscosity at 25°C measured with a rotational viscometer described in JIS K 7117-1:1999.

[0081] [Polysilazane compound-containing composition] As the polysilazane compound-containing compositions, the following PSZ-1 to PSZ-4 were used.

[0082] (PSZ-1) Product name: "X-45-870" [Dibutyl ether solution containing perhydropolysilazane], manufactured by Shin-Etsu Chemical Co., Ltd. The polysilazane compound is 20 mass% relative to the total amount of the polysilazane compound and the organic solvent (20% polysilazane component solution). It contains 1% curing catalyst. The weight average molecular weight of the polysilazane compound is 3000. Since it does not contain the repeating unit represented by the above formula (2), the ratio of the number of repeating units represented by formula (2) to the total number of repeating units represented by formula (1) and formula (2) is 0.

[0083] (PSZ-2) Product name "X-45-872" [Dibutyl ether solution containing perhydropolysilazane and methylpolysilazane], manufactured by Shin-Etsu Chemical Co., Ltd. The ratio of the number of repeating units represented by formula (2) to the total number of repeating units represented by formulas (1) and (2) (hereinafter referred to as "methylpolysilazane ratio") is 0.5. The polysilazane compound is 20 mass% relative to the total amount of the polysilazane compound and the organic solvent (20% polysilazane component solution). It contains 1% curing catalyst. The weight average molecular weight is 1500.

[0084] (PSZ-3) This is a product with a methylpolysilazane ratio of 0.25 compared to the product name "X-45-872" [dibutyl ether solution containing perhydropolysilazane and methylpolysilazane] (manufactured by Shin-Etsu Chemical Co., Ltd.). The polysilazane compound is 20 mass% based on the total amount of polysilazane compound and organic solvent (20% polysilazane component solution). It contains 1% curing catalyst. The weight average molecular weight is 1800.

[0085] (PSZ-4) Product name "X-45-872" [Dibutyl ether solution containing perhydropolysilazane and methylpolysilazane], manufactured by Shin-Etsu Chemical Co., Ltd., with a methylpolysilazane ratio of 0.7. The polysilazane compound is 20 mass% based on the total amount of polysilazane compound and organic solvent (20% polysilazane component solution). It contains 1% curing catalyst. The weight average molecular weight is 1700.

[0086] [Inorganic oxide particles] As the inorganic oxide particles, the following inorganic oxide particles-1 to inorganic oxide particles-5 were used.

[0087] (Inorganic oxide particles-1) Product name: "CR-50" [titanium oxide powder], manufactured by Ishihara Sangyo Kaisha.

[0088] (Inorganic oxide particles-2)

[0089] Product name: "Zinc Oxide" [Zinc oxide powder], manufactured by Mitsui Mining & Smelting. (Inorganic oxide particles-3)

[0090] Product name: "TZ-3YS-E" [Zirconium oxide], manufactured by Tosoh. (Inorganic oxide particles-4)

[0091] Product name: "ACT-05" [Silicon dioxide], manufactured by Fumitec.

[0092] (Inorganic oxide particles-5) Product name: "AO-502" [Aluminum oxide], manufactured by Admatechs.

[0093] [Synthesis Example 1] In a 300 mL eggplant flask, 10 g of the above PSZ-1, i.e., the polysilazane compound-containing composition "X-45-870", was weighed out, and 190 g of dibutyl ether was added to prepare a 1% polysilazane solution. After heating and stirring at 70°C for 1 hour, 100 g of inorganic oxide particles-1 was added, and the mixture was heated and stirred for another 3 hours. The treatment solution was removed by pressure filtration, and heat treatment was performed at 250°C for 4 hours to obtain surface-treated inorganic oxide particles 1 (D-1).

[0094] [Synthesis Example 2] Surface-treated inorganic oxide particles 2 (D-2) were obtained by carrying out the same procedure as in Synthesis Example 1, except that the polysilazane compound-containing composition "X-45-870" was replaced with the above PSZ-2, i.e., "X-45-872."

[0095] [Synthesis Example 3] The same operation was carried out except that the polysilazane compound-containing composition "X-45-870" of Synthesis Example 1 was replaced with the above PSZ-3, that is, "the methylpolysilazane ratio of X-45-872 was changed to 0.25", to obtain surface-treated inorganic oxide particles 3 (D-3).

[0096] [Synthesis Example 4] In a 300 mL eggplant flask, 50 g of the above PSZ-1, i.e., the polysilazane compound-containing composition "X-45-870", was weighed out, and 150 g of dibutyl ether was added to prepare a 10% polysilazane solution. After heating and stirring at 70°C for 1 hour, 100 g of inorganic oxide particles-1 was added, and the mixture was heated and stirred for another 3 hours. The treatment solution was removed by pressure filtration, and heat treatment was performed at 250°C for 4 hours to obtain surface-treated inorganic oxide particles 4 (D-4).

[0097] [Synthesis Example 5] Surface-treated inorganic oxide particles 5 (D-5) were obtained by carrying out the same procedure as in Synthesis Example 1, except that inorganic oxide particles-2 were used instead of inorganic oxide particles-1.

[0098] [Synthesis Example 6] Surface-treated inorganic oxide particles 6 (D-6) were obtained by carrying out the same procedure as in Synthesis Example 1, except that inorganic oxide particles-1 were replaced with inorganic oxide particles-3.

[0099] [Synthesis Example 7] Surface-treated inorganic oxide particles 7 (D-7) were obtained by carrying out the same procedure as in Synthesis Example 1, except that inorganic oxide particles-1 were changed to inorganic oxide particles-4.

[0100] [Synthesis Example 8] Surface-treated inorganic oxide particles 8 (D-8) were obtained by carrying out the same procedure as in Synthesis Example 1, except that inorganic oxide particles-5 were used instead of inorganic oxide particles-1.

[0101] [Comparative Synthesis Example 1] In a 300 mL eggplant flask, 10 g of the above PSZ-4, i.e., the polysilazane compound-containing composition "X-45-872" with a methylpolysilazane ratio of 0.7, was weighed out, and 190 g of dibutyl ether was added to prepare a 1% polysilazane solution. After heating at 70°C for 1 hour, 100 g of inorganic particles-1 was added, and the mixture was heated and stirred for another 3 hours. The treatment solution was removed by pressure filtration, and heat treatment was performed at 250°C for 4 hours to obtain surface-treated inorganic oxide particles 9 (D-9).

[0102] [Comparative Synthesis Example 2] Surface-treated inorganic oxide particles 10 (D-10) were obtained by carrying out the same procedure as in Comparative Synthesis Example 1, except that inorganic oxide particles-2 were used instead of inorganic oxide particles-1.

[0103] [Comparative Synthesis Example 3] Surface-treated inorganic oxide particles 11 (D-11) were obtained by carrying out the same procedure as in Comparative Synthesis Example 1, except that inorganic oxide particles-1 were replaced with inorganic oxide particles-3.

[0104] [Comparative Synthesis Example 4] Surface-treated inorganic oxide particles 12 (D-12) were obtained by carrying out the same procedure as in Comparative Synthesis Example 1, except that inorganic oxide particles-1 were changed to inorganic oxide particles-4.

[0105] [Comparative Synthesis Example 5] Surface-treated inorganic oxide particles 13 (D-13) were obtained by carrying out the same procedure as in Comparative Synthesis Example 1, except that inorganic oxide particles-1 were replaced with inorganic oxide particles-5.

[0106] [Comparative Synthesis Example 6] 10 g of silane coupling agent "KBM-04" (manufactured by Shin-Etsu Chemical Co., Ltd.) was weighed into a 300 mL eggplant-shaped flask and 190 g of toluene was added to prepare a 5% silane coupling agent solution. After heating at 100°C for 1 hour, 100 g of inorganic oxide particles-1 was added and heated and stirred for an additional 3 hours. The treatment solution was removed by pressure filtration, and heat treatment was performed at 150°C for 1 hour to obtain surface-treated inorganic oxide particles 14 (D-14).

[0107] [Comparative Synthesis Example 7] 10 g of the silane coupling agent "Ethyl Polysilicate 40T" (Colcoat Co., Ltd., tetraethoxysilane partial hydrolysis condensate) was weighed out into a 300 mL eggplant-shaped flask and 190 g of toluene was added to prepare a 5% solution. After heating at 100°C for 1 hour, 100 g of inorganic oxide particles-1 was added and heated and stirred for an additional 3 hours. The treatment solution was removed by pressure filtration, and heat treatment was performed at 150°C for 1 hour to obtain surface-treated inorganic oxide particles 15 (D-15).

[0108] [Example 1] The component (A) is an organopolysiloxane represented by the following formula (A-1): [ka] 50 copies, The component (B) is an organohydrogenpolysiloxane represented by the following formula (B-1): [ka] such that the ratio of the total number of silicon-bonded hydrogen atoms in component (B-1) to the total number of silicon-bonded vinyl groups in component (A-1) (hereinafter sometimes referred to as the SiH / SiVi ratio) is 2.0 (in this case, 1 part by mass). (C) 0.1 part of an octyl alcohol denatured solution of chloroplatinic acid (elemental platinum content: 1% by mass) As component (D), 50 parts of the prepared surface-treated inorganic oxide particles-1 (D-1) The mixture was added and thoroughly stirred to prepare an addition-curable silicone composition. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0109] [Example 2] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 50 parts of surface-treated inorganic oxide particles-2 (D-2) were used as component (D) instead of 50 parts of surface-treated inorganic oxide particles-1 (D-1) used in Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0110] [Example 3] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 50 parts of surface-treated inorganic oxide particles-3 (D-3) were used as component (D) instead of 50 parts of surface-treated inorganic oxide particles-1 (D-1) used in Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0111] [Example 4] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 50 parts of surface-treated inorganic oxide particles-4 (D-4) were used as component (D) instead of 50 parts of surface-treated inorganic oxide particles-1 (D-1) used in Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0112] [Example 5] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 50 parts of surface-treated inorganic oxide particles-5 (D-5) were used as component (D) instead of 50 parts of surface-treated inorganic oxide particles-1 (D-1) used in Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0113] [Example 6] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 50 parts of surface-treated inorganic oxide particles-6 (D-6) were used as component (D) instead of 50 parts of surface-treated inorganic oxide particles-1 (D-1) used in Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0114] [Example 7] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 50 parts of surface-treated inorganic oxide particles-7 (D-7) were used as component (D) instead of 50 parts of surface-treated inorganic oxide particles-1 (D-1) used in Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0115] [Example 8] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 50 parts of surface-treated inorganic oxide particles-8 (D-8) were used as component (D) instead of 50 parts of surface-treated inorganic oxide particles-1 (D-1) used in Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0116] [Example 9] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 30 parts of the organopolysiloxane (A-1) used in Example 1 was used as the component (A) instead of 50 parts, and 70 parts of the surface-treated inorganic oxide particles-1 (D-1) used in Example 1 were used as the component (D) instead of 50 parts. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0117] [Example 10] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Example 1, except that 70 parts of the organopolysiloxane (A-1) used in Example 1 was used as the component (A) instead of 50 parts, and 30 parts of the surface-treated inorganic oxide particles-1 (D-1) used in Example 1 were used as the component (D) instead of 50 parts. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 1.

[0118] [Comparative Example 1] The component (A) is an organopolysiloxane represented by the following formula (A-1): [ka] 50 copies, The component (B) is an organohydrogenpolysiloxane represented by the following formula (B-1): [ka] in an amount such that the ratio of the total number of silicon-bonded hydrogen atoms in component (B-1) to the total number of silicon-bonded vinyl groups in component (A-1) (SiH / SiVi ratio) is 2.0 (C) 0.1 part of an octyl alcohol denatured solution of chloroplatinic acid (elemental platinum content: 1% by mass) As component (D), 50 parts of untreated inorganic oxide particles-1 The mixture was added and thoroughly stirred to prepare an addition-curable silicone composition. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0119] [Comparative Example 2] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of inorganic oxide particles-2 were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0120] [Comparative Example 3] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of inorganic oxide particles-3 were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0121] [Comparative Example 4] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of inorganic oxide particles-4 were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0122] [Comparative Example 5] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of inorganic oxide particles-5 were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0123] [Comparative Example 6] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of surface-treated inorganic oxide particles-9 (D-9) were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0124] [Comparative Example 7] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of surface-treated inorganic oxide particles-10 (D-10) were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0125] [Comparative Example 8] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of surface-treated inorganic oxide particles-11 (D-11) were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0126] [Comparative Example 9] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of surface-treated inorganic oxide particles-12 (D-12) were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0127] [Comparative Example 10] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of surface-treated inorganic oxide particles-13 (D-13) were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0128] [Comparative Example 11] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of surface-treated inorganic oxide particles-14 (D-14) were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0129] [Comparative Example 12] An addition-curable silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 50 parts of surface-treated inorganic oxide particles-15 (D-15) were used as component (D) instead of 50 parts of inorganic oxide particles-1 used in Comparative Example 1. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0130] [Comparative Example 13] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 30 parts of the organopolysiloxane (A-1) used in Comparative Example 1 was used as the component (A) instead of 50 parts, and 70 parts of the inorganic oxide particles-1 used in Comparative Example 1 were used as the component (D) instead of 50 parts. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0131] [Comparative Example 14] An addition curing silicone composition was obtained by preparing a composition in the same manner as in Comparative Example 1, except that 70 parts of the organopolysiloxane (A-1) used in Comparative Example 1 was used as the component (A) instead of 50 parts, and 30 parts of the inorganic oxide particles-1 used in Comparative Example 1 were used as the component (D) instead of 50 parts. This composition was molded by heating at 150°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the following physical properties were measured. The results are shown in Table 2.

[0132] The physical properties of each of the compositions prepared in Examples 1 to 8 and Comparative Examples 1 to 14 and their cured products were measured by the following methods. The results are shown in Tables 1 and 2.

[0133] (1) Appearance Each composition was cured at 150° C. for 4 hours, and the color, transparency, and presence or absence of voids of the resulting cured product (1 mm) were visually inspected.

[0134] (2) Properties The fluidity of each composition before curing was confirmed. 50 g of the composition was added to a 100 ml glass bottle, which was then turned on its side and left to stand at 25°C for 10 minutes. If the resin flowed out during that time, it was determined to be liquid.

[0135] (3) Viscosity The viscosity of each composition before curing at 25° C. was measured by the method described in JIS K 7117-1:1999.

[0136] (4) Thixotropy The viscosity at 10 rpm and the viscosity at 1 rpm of each composition before curing at 25° C. were measured by the method described in JIS K 7117-1:1999, and the thixotropic ratio was calculated as 1 rpm viscosity / 10 rpm viscosity.

[0137] (5) Hardness (Type A) Each composition was cured at 150° C. for 4 hours, and the hardness of the cured product was measured using a durometer type A hardness tester in accordance with JIS K 6249:2003.

[0138] (6) Elongation at break and tensile strength Each composition was cured at 150° C. for 4 hours, and the hardness of the resulting cured product was measured in accordance with JIS K 6249:20003.

[0139] (7) Heat resistance test Each composition was cured at 150°C for 4 hours, and the resulting cured product was left in air at 250°C for 1000 hours to check the change in hardness. In addition, the resin was applied to a slide glass (25mm x 75mm x 1mm) to a thickness of 250μm, and similarly cured at 150°C for 4 hours. The resulting cured product was left in air at 250°C for 1000 hours, and the appearance was checked. (Appearance criteria) ○: No cracks observed △: Some cracks are visible ×: Cracks are observed

[0140] (8) Moisture resistance test Each composition was cured at 150°C for 4 hours, and the resulting cured product was left in the air at 135°C and 85% Rh, and the HAST test was performed for 1000 hours to confirm the change in hardness. In addition, the resin was applied to a thickness of 250 μm on a slide glass (25 mm x 75 mm x 1 mm), and similarly cured at 150°C for 4 hours. The resulting cured product was left in the air at 135°C and 85% Rh, and the HAST test was performed for 1000 hours to confirm the appearance. (Appearance criteria) ○(Good): No cracks observed △ (slightly poor): some cracks are visible × (bad): Cracks are visible

[0141] [Table 1]

[0142] [Table 2]

[0143] As shown in Table 1, in Examples 1 to 10, in which surface-treated inorganic oxide particles satisfying the conditions of the present invention were used as component (D), cured products excellent in sufficient viscosity, appearance, tensile strength, elongation at break, heat resistance, moisture resistance, and crack resistance were obtained. In contrast, in Comparative Examples 1 to 5, in which inorganic oxide particles not treated with a polysilazane compound were used, the viscosity was high, there was a problem with workability, and furthermore, the hardness of the cured product significantly increased after the heat resistance and moisture resistance tests, and cracks also occurred in the resin. In addition, in Comparative Examples 6 to 10, in which surface-treated inorganic oxide particles treated with a polysilazane compound that does not satisfy the specified range, which is the condition of the present invention, an increase in hardness of the cured product after the heat resistance test (deterioration of heat resistance) and an increase in resin viscosity were observed. Furthermore, in Comparative Examples 11 to 12, in which surface-treated inorganic oxide particles treated with a commonly used silane coupling agent were used, a sufficient decrease in viscosity was observed, but there were problems with heat resistance, moisture resistance, and crack resistance. In Comparative Example 13, in which the content of inorganic oxide particles was increased, there was also a problem of voids occurring in the cured product due to a significant increase in viscosity and thixotropy ratio. In Comparative Example 14, the content of inorganic oxide particles was reduced, but no improvement in heat resistance, moisture resistance, or crack resistance was observed. As described above, the addition-curable silicone composition of the present invention can provide a cured product that is excellent in workability, mechanical properties, heat resistance, moisture resistance, and crack resistance.

[0144] This specification includes the following inventions.

[0145] [1]: (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in the component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in the component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles An addition-curable silicone composition comprising: The addition-curable silicone composition is characterized in that the inorganic oxide particles are surface-treated inorganic oxide particles that contain a polysilazane compound and an organic solvent, in which the ratio of the number of repeating units represented by the following formula (2) to the total number of repeating units represented by the following formulas (1) and (2) is 0 to 0.5, and the polysilazane compound is present in an amount of 0.1 to 20 mass% relative to the total amount of the polysilazane compound and the organic solvent. [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and R in one molecule of the polysilazane compound may be the same or different.) [2]: The addition-curable silicone composition according to the above [1], wherein R in the formula (2) in the polysilazane compound is a methyl group. [3]: The addition-curable silicone composition according to the above [1] or [2], wherein the polysilazane compound-containing composition contains a curing catalyst. [4]: The addition-curable silicone composition according to any one of [1] to [3] above, wherein the inorganic oxide particles contain at least one of silicon dioxide, zirconium oxide, titanium oxide, aluminum oxide, and zinc oxide. [5]: An optical semiconductor device comprising a cured product obtained by curing the addition-curable silicone composition according to any one of [1] to [4] above. [6]: (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in the component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in the component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles A method for producing an addition-curable silicone composition comprising the steps of: providing the inorganic oxide particles; a step of preparing surface-treated inorganic oxide particles by surface-treating the inorganic oxide particles with a polysilazane compound-containing composition containing a polysilazane compound and an organic solvent, the polysilazane compound being present in an amount of 0.1 to 20 mass% relative to the total amount of the polysilazane compound and the organic solvent, the polysilazane compound being in a ratio of 0.5 to 0.5, and the inorganic oxide particles being in a ratio of 0.1 to 20 mass% relative to the total amount of the polysilazane compound and the organic solvent; a step of producing the addition-curable silicone composition by mixing the surface-treated inorganic oxide particles with the components (A) to (C); 2. A method for producing an addition-curable silicone composition comprising the steps of: [ka] (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and R in one molecule of the polysilazane compound may be the same or different.)

[0146] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles An addition-curable silicone composition comprising: The inorganic oxide particles are surface-treated inorganic oxide particles that contain a polysilazane compound and an organic solvent, the ratio of the number of repeating units represented by the following formula (2) to the total number of repeating units represented by the following formulas (1) and (2) being 0 to 0.5, and the polysilazane compound is present in an amount of 0.1 to 20 mass % relative to the total amount of the polysilazane compound and the organic solvent. 【Chemistry 1】 (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and R in one molecule of the polysilazane compound may be the same or different.)

2. 2. The addition-curable silicone composition according to claim 1, wherein R in the polysilazane compound of formula (2) is a methyl group.

3. 2. The addition-curable silicone composition according to claim 1, wherein the polysilazane compound-containing composition contains a curing catalyst.

4. 2. The addition-curable silicone composition according to claim 1, wherein the inorganic oxide particles include at least one of silicon dioxide, zirconium oxide, titanium oxide, aluminum oxide, and zinc oxide.

5. An optical semiconductor device comprising a cured product obtained by curing the addition-curable silicone composition according to claim 1 .

6. (A) an organopolysiloxane having two or more alkenyl groups having 2 to 10 carbon atoms bonded to silicon atoms per molecule; (B) an organosilicon compound having two or more silicon-bonded hydrogen atoms per molecule: an amount such that the number of silicon-bonded hydrogen atoms in component (B) is 0.1 to 4.0 moles per mole of alkenyl groups in component (A); (C) a platinum group metal catalyst: a catalytic amount, and (D) Inorganic oxide particles A method for producing an addition-curable silicone composition comprising the steps of: providing the inorganic oxide particles; a step of preparing surface-treated inorganic oxide particles by subjecting the inorganic oxide particles to a surface treatment with a polysilazane compound-containing composition containing a polysilazane compound and an organic solvent, the polysilazane compound being present in an amount of 0.1 to 20 mass % relative to the total amount of the polysilazane compound and the organic solvent, the polysilazane compound being 0.1 to 20 mass % relative to the total amount of the polysilazane compound and the organic solvent; producing the addition-curable silicone composition by mixing the surface-treated inorganic oxide particles with the components (A) to (C); 2. A method for producing an addition-curable silicone composition comprising the steps of: 【Chemistry 2】 (In the formula, R is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an aromatic hydrocarbon group having 6 to 12 carbon atoms, and an alkoxy group having 1 to 6 carbon atoms, and R in one molecule of the polysilazane compound may be the same or different.)

Citation Information

Patent Citations

  • Optical waveguiding plate, and silicone rubber composition for the same

    JP2010083978A

  • Hygroscopic silicone resin composition, transparent sealant for organic el, transparent drying agent for organic el, and method for using them

    JP2020084028A

  • Curable organopolysiloxane composition and semiconductor device

    JP2006213789A

  • Curable silicone composition

    JP2007131694A

  • Isocyanuric ring-containing terminal vinyl polysiloxane

    JP2011099008A